First-principles study on the structural, elastic, electronic and optical properties of lead-free double perovskites Cs2CuBiX6 (XI, Br, Cl). (December 2021) - Hu, De-Yuan; Zhao, Xian-Hao; Tang, Tian-Yu; Lu, Li-Min; Li, Li; Gao, Li-Ke; Tang, Yan-Lin
Abstract: In this paper, the structural, elastic, electronic and optical properties of lead-free double perovskites Cs2 CuBiX6 (XI, Br, Cl) were studied by using first-principles calculations. The negative binding energies (Eb ) and formation energies (Ef ) show that Cs2 CuBiX6 can be synthesized and they meet thermodynamic stability. The Cauchy's pressures of double perovskites Cs2 CuBiX6 are positive, which indicate that these three perovskites are ionic crystals. The calculated results of Pugh's ratio (B/G) and Poisson's ratio (υ) reveal that the three perovskite materials are all ductile compounds. Furthermore, these three perovskite materials are all anisotropic. The results show that double perovskites Cs2 CuBiX6 are indirect band gap semiconductors. The band gap values of double perovskites Cs2 CuBiX6 (XI, Br, Cl) are 0.78 eV, 1.13 eV and 1.29 eV, respectively, which are appropriate for photosensitive materials of solar cells. In addition, the effective mass values of electrons and holes of these three perovskite materials are very small, which is conducive to the transport of carriers. In the study of optical properties, we found that these three perovskite materials have better absorption performance for visible light. Due to the appropriate band gaps and prominent light absorption, the lead-free double perovskites Cs2 CuBiX6 can be potential candidates for lead-free photovoltaic materials. Graphical Abstract: ga1 Highlights: First-principles method was adopted to study the structural, elastic, electronic and optical properties of lead-free double perovskites Cs2 CuBiX6 (XI, Br, Cl). The band gap values of double perovskites Cs2 CuBiX6 (XI, Br, Cl) are 0.78 eV, 1.13 eV and 1.29 eV, respectively, which are appropriate for photosensitive materials of solar cells. In the study of optical properties, we found that the double perovskites Cs2 CuBiX6 (XI, Br, Cl)have better absorption performance for visible light, so they have great potential to be applied to the absorber layer of solar cells.